Association of Postoperative Glycemic Control with Outcomes after Carotid Procedures - Bath, Jonathan (Vascular, 2019)
OBJECTIVE: There are limited data evaluating the impact of postoperative hyperglycemia in patients undergoing vascular procedures. This study evaluated the relationship between suboptimal glucose control and adverse outcomes after carotid artery stenting (CAS) and carotid endarterectomy (CEA). METHODS: Patients admitted for elective carotid procedures were selected from the Cerner Health Facts® (2008–2015) database using ICD-9-CM diagnosis and procedure codes. We examined the relationship between patient characteristics, postoperative hyperglycemia (any value >180 mg/dL), and complications with chi-square analysis. A multivariable model examined the association between patient characteristics, procedure type, and glucose control with infection, renal failure, stroke, respiratory and cardiac complications, and length of stay (LOS) over 10 days. RESULTS: Of the 4,287 patients admitted for an asymptomatic carotid procedure, 788 (18%) underwent CAS and 3,499 (82%) underwent CEA. Most patients (87%) had optimal postoperative glucose control (80–180 mg/dL); 13% had suboptimal glucose control. On average, patients with suboptimal glucose control experienced: higher stroke rates (6.2% vs. 2.7%; p < 0.001); more cardiac complications (5.1% vs. 2.0%; p < 0.001); longer hospital stays (3.1vs.1.8 days; p< .001); higher rates of post-procedure infection (4.0% vs.1.8%; p=.001); and more complications than patients with optimal glucose control. Multivariable logistic regression demonstrated that patients with suboptimal glucose control had higher odds of having an infectious (pneumonia, cellulitis, surgical site etc.) complication (OR 1.91, 95% CI 1.10–3.34), renal failure (OR 3.36, 95% CI 1.95–5.78), respiratory complications (OR 1.81, 95% CI 1.21–2.71), stroke (OR 1.82, 95% CI 1.15–2.88), or LOS>10 days (OR 4.07, 95% CI 2.02–8.20). CONCLUSIONS: Suboptimal glucose control was associated with adverse events after CAS and CEA, independent of a diabetes diagnosis. Several adverse outcomes were associated with hyperglycemia, including stroke. Given the singular role of carotid procedures in preventing stroke, we suggest that incorporating rigorous post-operative glucose control into best medical treatment of carotid disease should be considered as standard practice.